Kryzys gospodarczy czy kryzys moralny? Refleksja w świetle nauczania społecznego Kościoła - Stępniak, ks. Marek (Annales. Etyka w Życiu Gospodarczym, 2012)
We shall look for the essence of the contemporary crisis: whether it is only the economic crisis which results in the drop of income, production, demand, crash on the stock exchange and the spectre of bankruptcy of whole states, or whether the economic phenomena originate in the sphere of human spirit and moral values, acquired insufficiently or simply questioned. We put forward a thesis that the economic crisis has its source in the sphere of spirit. Denying the natural law and God’s law included in the Ten Commandments does not make a man happy but introduces divisions, social conflicts and exploitation. For that reason the moral renewal of individuals and societies, showing respect for the dignity of a human being and his/her natural rights must go along with reasonable political and economic actions for the sake of solving the contemporary ‘social issue’. Without moral renewal any other solutions, sooner or later shall turn against a man and cause irreparable damages.